2011
DOI: 10.3109/09546634.2011.594871
|View full text |Cite
|
Sign up to set email alerts
|

Instant barrier repair: a pilot study investigating occlusion with a new hydrogel patch for the treatment of atopic dermatitis

Abstract: The ideal repair mechanism for overcoming barrier disruption in atopic dermatitis (AD) needs to completely eliminate microbe and allergen penetration as well as transepidermal water loss. We propose the hydrogel patch as an innovative approach to complete barrier repair. It is composed of an adhesive, thin, flexible, hydrogel layer on an impermeable urethane surface. We conducted a 6-week pilot study with 15 AD patients, who applied the hydrogel patch over one lesion for 6-8 h daily and triamcinolone (TAC) 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…A typical child will require 150-200 g of emollient on a weekly basis, and adults may require up to 500 g. Emollients containing potential allergens such as peanut, oat, and shea nut should be avoided since the skin can serve as entry for allergic sensitization [ 46 ]. A recent pilot study of 15 AD patients using a hydrogel compound under occlusion demonstrated similar efficacy to use of triamcinolone 0.1 %, supporting the concept that restoration of barrier function is an imperative treatment objective [ 49 ].…”
Section: Treatmentsmentioning
confidence: 96%
“…A typical child will require 150-200 g of emollient on a weekly basis, and adults may require up to 500 g. Emollients containing potential allergens such as peanut, oat, and shea nut should be avoided since the skin can serve as entry for allergic sensitization [ 46 ]. A recent pilot study of 15 AD patients using a hydrogel compound under occlusion demonstrated similar efficacy to use of triamcinolone 0.1 %, supporting the concept that restoration of barrier function is an imperative treatment objective [ 49 ].…”
Section: Treatmentsmentioning
confidence: 96%
“…In a pilot study of 15 patients, Park et al (2011) evaluated the efficacy and safety of a hydrogel patch for AD treatment. The hydrogel patch used in this study was composed of an adhesive, thin, flexible, hydrogel layer on an impermeable urethane surface.…”
Section: Hydrogel Patchmentioning
confidence: 99%
“…This study appears to demonstrate that instant correction of the dysfunctional skin barrier with the hydrogel patch can improve signs and symptoms of AD comparable to TAC 0.1% cream. Thus, the hydrogel patch may provide a new approach to occlusive therapy without the potential risks of topical corticosteroid use (Park et al 2011) 3.4 Cutaneous and systemic side effects Topical corticosteroid use can cause both cutaneous and systemic side effects, most significantly laboratory adrenal insufficiency. Risk factors include the use of high potency corticosteroids, occlusive or prolonged therapy, and application to thin-or barriercompromised skin lesions.…”
Section: Hydrogel Patchmentioning
confidence: 99%
See 2 more Smart Citations